If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 5s + -82s = 22s Combine like terms: 2s + 5s = 7s 7s + -82s = 22s Combine like terms: 7s + -82s = -75s -75s = 22s Solving -75s = 22s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-22s' to each side of the equation. -75s + -22s = 22s + -22s Combine like terms: -75s + -22s = -97s -97s = 22s + -22s Combine like terms: 22s + -22s = 0 -97s = 0 Divide each side by '-97'. s = 0 Simplifying s = 0
| -2/(x^2) | | 3(X+4)=2X-23 | | 13.00-7.28= | | -5n-19=-6n-13+3n | | 8=6x-4x+4 | | 2s+5w=5sw | | 5k+3=73 | | 14x-18=32-22x | | 5x+10=9X+16 | | -15-10z=-13z | | 3(2y+3)-4=-9 | | 2h+9.7=-9.7 | | -9(-6x-5)=30(-7+8x) | | 45-15k= | | 4j^2+9j+3=0 | | k/5+81.8=47.2 | | 2c-4=17+5c | | 2x-5/3x-3=1/2 | | 8k+3=2k+33 | | 4x^2+4y^2=27 | | -4.2x+31=-53 | | 3x-3-3=24 | | 5.5x-5=-60 | | 5v-6=-21 | | 13=3u+7 | | 30=9.6x | | 6x(360/4) | | 7w^2-3w-9=0 | | 5(s+2t)+2(3s-t)= | | -4+3x=5x | | 0.66x=5 | | 83.7(-723.7)= |